Políticas públicas e reservas da biosfera, desafios na gestão de cidades brasileiras - Neli Aparecida de Mello-Théry; Hervé Théry (Confins)
The challenge of planning and urban public policies is, in contemporary times, to find ways of dealing with fragmentation, a process present in Brazilian and Latin American cities. The urban spaces are marked by pollution, noise, congestion, precarity and lack of infrastructure. It is necessary, therefore, to understand the urban dynamics both in the scale of districts and of the city in its totality. The analysis of the impacts of this fragmentation is an essential condition to identify and propose mechanisms for urban sustainability, environments quality and to make cities more inclusive. We have identified as a starting point that mechanisms such as biosphere reserves can serve as models. The questions addressed in this work have the objective of proposing ways to be incorporated in urban policies and environmental planning, in order to contribute to the changes in the socio-spatial configurations of the present cities.